The Representation of the Figurative Movement as a Civilizing Strategy of Egyptian Art: The Figuration of Private Tombs Before and After Amarnian Art - Hernández Figueroa, María Isabel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The origin of the Egyptian canonical figure takes place in the pre-dynastic periods, and arises after a process of graphic conceptualization. It will be in the dynastic phase when this model is standardized, and begins to gradually incorporate some human elements related to gesture and movement, especially during the 18th Dynasty. These are central characteristics because they encode a whole universe of social manners relative to Egyptian individuals who live organized in the form of a State. Thus, the figures are increasingly representative of the human, so they enhance their ability to organize and classify the anthropological.